The Natuna Regent's Leadership Style in 2021-2024 Period: A Leadership Characterized by Archipelagic Region - Taslim Djafar (Institut Pemerintahan Dalam Negeri, 2023)
This research analyzed and described the leadership style of the Natuna Regent during the 2021-2024 period, which is characterized by the archipelagic regions. To achieve this, the Thoha theory comprising four types of leadership styles, namely directive, consultative, participative, and delegation, was employed. Furthermore, a qualitative approach with a descriptive design was employed, with data collected through interviews, observations, and documentation. The collected data were subsequently analyzed through data reduction and by drawing conclusions.The results showed that the Natuna Regent exhibits a collaborative leadership style that encompasses all four styles tailored to the specific needs of the organization. Supporting factors include the Regent's in-depth understanding of governance issues, non-authoritarian approach, welcoming attitude, strong communication skills, and encouragement of innovative ideas from all individuals. However, inhibiting factors include certain Regional Apparatus Organizations (RAO) that have not fully fulfilled their responsibilities, subordinates or RAO displaying unresponsiveness towards directives, and program implementation lacking sufficient support from the regional budget. Efforts to overcome these inhibiting factors in the leadership style of the Natuna Regent include encompassing consolidating relationships with all regional apparatus, establishing a shared mission and vision, fostering innovation among the regional apparatus and RAO heads, promoting collaboration through the Regional Leadership Coordination Forum (Forkopimda), and ensuring seamless task execution without obstacles.